The influence of domestic workers on the brand equity of homecare products in South African households - Dube, Sibonile (My University, 2016)
Since 1994, the number of South Africans who have the ability to hire domestic help has increased due to the economic inclusion of the African majority. This research has been conducted amongst South Africa’s middle to upper class (also referred to as LSM 7-10 or LSM A). A sizeable number of them have a monthly household income of R50 000 and above and another significant number is made up of business owners. The aim of the study is to assess the extent to which domestic workers’ perceived brand quality of homecare products influence the brand loyalty of the same as far as their employers are concerned. The data collection of this study was exclusively conducted online for the simple reason that the target population of the study is made up of office bound and busy people. A large majority of the respondents in fact spend 4-5 hours in their homes per day during the week. Therefore expecting them to fill in a questionnaire and submit to the researcher would have been a challenge. The research’s point of departure was based on the assumption that employers of domestic workers are not the end users of the products under discussion as their lifestyle did not permit this. However, the fact that the employers are the eventual buyers of the products presented the researcher with a point of curiosity. The key finding of the research was that there was a very strong link between Employer Brand Association and Employer Brand Loyalty. However, there was a weak influence of Employer Brand Awareness on Employer Brand Loyalty. These findings therefore ultimately suggest that domestic worker Brand Quality perceptions, will influence the Brand Equity of homecare products in South Africa. Overall, the Domestic Worker Perceived Brand Quality of homecare products had a positive influence on Employer Brand Awareness and Employer Brand Associations
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing 2016
Keywords: Consumer behavior--South Africa; Brand name products--Marketing--South Africa; Household employees--South Africa; Cosmetics--Marketing--South Africa